CircSFXN1 regulates the behaviour of trophoblasts and likely mediates preeclampsia. (November 2020) - Zhang, Yonggang; Yang, Hongling; Zhang, Yipeng; Shi, Junzhu; Chen, Ronggui; Xiao, Xiaoqin
Abstract: Preeclampsia (PE) is the second most common complication that threatens the health of pregnant women and their foetuses; however, the underlying mechanisms are poorly understood. Circular RNAs (circRNAs) are involved in various human diseases, and an increasing number of studies have revealed the vital role of circRNAs in PE. Here, we investigated the biological function of circRNA-SFXN1 (CircSFXN1) in PE and the associated molecular mechanisms. Microarray data analysis revealed that CircSFXN1 was highly expressed in PE placentas compared to control placentas; this finding was confirmed by qRT-PCR. In vitro, CircSFXN1 overexpression significantly inhibited the invasion of TEV-1 trophoblasts and blocked the angiogenesis of human umbilical vein endothelial cells (HUVECs), while CircSFXN1 knockdown promoted trophoblast invasion and stimulated HUVEC angiogenesis. For in vivo evaluation, pregnant Sprague-Dawley rats were randomly selected for tail vein injection with sFLT1-expressing adenovirus, which resulted in elevated blood pressure and increased proteinuria; si-CircSFXN1 reversed these increases. Mechanistic analyses via RNA-protein pulldown, RNA immunoprecipitation (RIP) and dual-luciferase reporter assays showed that CircSFXN1 recruits sFLT1 and modulates the biological behaviour of trophoblasts by binding sFLT1. In summary, we identified a novel circRNA that regulates tumorigenic activities, suggesting a new pathway governing CircSFXN1/sFLT1-mediated regulation of trophoblast behaviour. Highlights: In this study, we present a novel CircSFXN1/sFLT1 axis regulatory mechanism, The context is novel and interesting. In the present study, we compared the expression of CircSFXN1 in placentas from preeclamptic and healthy pregnancies, examined the effects of one particular circRNA, circSFXN1, on trophoblast behaviour, and injected sFLT1 into pregnant rats to induce a preeclampsia-like phenotype; circSFXN1 reversed this activity. CircRNAs are a relatively new field of study, particularly in placental research, and this report details the substantial effects of circSFXN1 and is therefore potentially very interesting.